2006
DOI: 10.1016/j.otohns.2006.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Pylori: A Possible Association with Otitis Media with Effusion

Abstract: A-1b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 16 publications
1
62
1
Order By: Relevance
“…It is known to be present in the oropharyngeal area in subgingival plaques, dental plaques and saliva (1). In recent years, research has shown its presence in middle ear effusions and tonsil and adenoid tissues (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…It is known to be present in the oropharyngeal area in subgingival plaques, dental plaques and saliva (1). In recent years, research has shown its presence in middle ear effusions and tonsil and adenoid tissues (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Yılmaz et al [6] evaluated 22 children with OME (patient group) and 20 children who underwent surgery for other conditions (control group). They identified H. pylori in both the tonsil and adenoid samples by PCR and CLO methods.…”
Section: Correlation Among Pepsinogen Levels In Middle Ear Fluid and mentioning
confidence: 99%
“…The main question is whether the acidic pH and the presence of pepsin or the toxic effect of the presence of refluxed H. pylori is responsible for the pathological process. Yılmaz et al [6] investigated this issue by prescribing antibiotic and acid suppression therapy for H. pylori eradication. Amoxicillin and clarithromycin are used to eradicate H. pylori.…”
Section: Correlation Among Pepsinogen Levels In Middle Ear Fluid and mentioning
confidence: 99%
See 1 more Smart Citation
“…Yilmaz et al (2004) found H. pylori in middle ear effusions and in one adenoid tissue specimen using PCR (23S rRNA gene). Yilmaz et al (2006) found H. pylori in 64% of adenoid and tonsillar specimens by PCR (16S rRNA gene). Kusano et al (2007) showed H. pylori positivity in 126 (72.9%) tonsillar specimens using PCR (16S rRNA gene).…”
Section: H Pylori In Oropharyngeal Lymphatic Tissuementioning
confidence: 99%